Study about Using of Polymeric Materials for Improving Hand Hygiene Quality for Healthcare Staff. Issue 1 (21st August 2022) - Dinu, Eleonora; Repanovici, Angela; Nemet, Codruta
Abstract: The study aims to evaluate the quality of hand hygiene for different categories of employees in the health system. An analysis of the observance of the correct hand washing steps is performed using the observation method at six hospitals in Brasov, Romania. The results are compared with those obtained using the Semmelweis Scanner device, produced by the Hand in Scan company in Budapest; this is a digital control system. Immediate, objective feedback on the quality of the completion of the hand disinfection technique is obtained. The system requires Ultra Violet ‐UV‐ light. The aspect regarding the presence of polymeric materials like varnish and the nail polish on the nails of the medical staff is followed. The sample consists of 553 volunteers. There are no statistically significant differences between the three categories of healthcare staff when the compliance to the World Health Organization recommendations regarding nail hygiene is concerned (67.24% compliance in physicians compared to 66.10% in nurses and 67.60% in auxiliary staff, respectively). Surprisingly, the presence of gel coated nails is a protection factor with statistically significant p value after objectivation with Semmelweis scanner.